(untitled) (International Journal of Engineering and Computer Science, 2014)
Purpose of our application is to be used by banks for web-clients. Banks are always looking for more powerful and user-friendly applications to upgrade their existing websites. So, our hypothesis is that AI would perform on all platforms using artificial algorithms to analyze and understand user’s queries relating to the bank’s loan, account, policy etc. This shows that AI would perform as per design and expectation. No specific format would be required for the client to ask questions. For instance, the question “what is the interest on home loan?” can be framed as “Let me know about interest on home loan”. It has integrated text-to-speech concept & graphical representation of a person speaking out answers. It also consists of ATM finder and Branch locator systems for other bank related help.